Inclusiveness in Religion: UIN Sunan Kalijaga's Religious Laboratory for Local Wisdom and Harmony - Syihabuddin, Muhammad; Adi Pradana, Mahatva Yoga; Abdul Wafi, Hasan (Jurnal Dialog, 2024)
The inclusivity approach in religious studies emphasizes the importance of openness to the diversity of religious views and practices, which is considered capable of enriching interfaith dialogue. This paper seeks to see the face of UIN Sunan Kalijaga's Religious Laboratory as an important element and icon of equality and diversity in the frame of inclusiveness. This research uses a qualitative methodological approach with literature analysis and empirical observation to understand how this laboratory integrates inclusive values into religious education. The results show that the Inclusive Religion Laboratory has succeeded in creating an academic space that supports pluralism, interreligious dialog, and tolerance. This laboratory not only acts as a research center but also as a model for applying local wisdom in an academic context that respects diversity. In addition, the UIN Sunan Kalijaga Campus Mosque is also a symbol of openness and respect for diversity, which supports inclusivity efforts in the campus community. In conclusion, UIN Sunan Kalijaga's Inclusive Religion Laboratory is a concrete example of how local wisdom and religious values can be integrated into religious education to promote inclusivity, tolerance, and interfaith dialogue. This article suggests that other religious institutions adopt similar approaches to strengthen efforts to create harmony in a multicultural society. The implementation of inclusive values in religious education is expected to be the foundation for the creation of peace and tolerance among religious communities.